Reflexões sobre a construção do Ethos do psicopedagogo: uma experiência vivida no espaço de formação - Fernandes, Anete Maria Busin (2011)
The objective of this thesis is to reflect on formation in psychopedagogy, in other words, to contribute to the development of a field that will provide information on the construction of the profile of a psychopedagogist. This research has been carried out in connection with a course in psychopedagogical diagnosis, based on depositions of students regarding their experiences. This specialization course in psychopedagogy at the Catholic University of São Paulo was the first contact that many of the students have had with clinical practice. A team of supervisors monitors and counsels them on their handing of clinical cases as these students accompany their clients in a process based on weekly contacts. This present thesis is qualitative in nature, based on intervention-research, using the potential space method, as first set up by Donald Winnicott. The research was carried out on students taking the specialization course in psychopedagogy and who participated in the construction of psychopedagogical situations using the "sand game" procedure. The theoretical frame of reference was obtained by joining aspects of the theories Winnicott and Gilberto Safra, with references also to Edith Stein's theories. The central focus is to see formation as an activity in the area of ethics and aesthetics, which the author considers preferable to a technical or mechanistic approach. The question of this thesis can be broken down into two main points: (a) What conditions are necessary in this intermediate area, where psychopedagogist and patient come together, in order to begin a process of creation and appropriation of therapeutic practices? and (b) What relationship might this practice have with the construction of professional ethos? Based on Edith Stein, the author conceives ethos as the construction of a professional place in a movement that occurs in the individual, from inside to outside